Expression of the plasma membrane citrate carrier (pmCiC) in human cancerous tissues—correlation with tumour aggressiveness - Schwertner, Barbara; Dahdal, George; Jagla, Wolfgang; Grossmann, Luis; Drexler, Konstantin; Krahn, Michael P.; Evert, Katja; Berneburg, Mark; Haferkamp, Sebastian; Ziegler, Christine; Parkinson, Eric K.; Zahn, Grit; et al. (Frontiers in Cell and Developmental Biology, 2024)
We have recently shown that cancer cells of various origins take up extracellular citrate through the plasma membrane citrate carrier (pmCiC), a specific plasma membrane citrate transporter. Extracellular citrate is required to support cancer cell metabolism, in particular fatty acid synthesis, mitochondrial activity, protein synthesis and histone acetylation. In addition, cancer cells tend to acquire a metastatic phenotype in the presence of extracellular citrate. Our recent study also showed that cancer-associated stromal cells synthesise and release citrate and that this process is controlled by cancer cells. In the present study, we evaluated the expression of pmCiC, fibroblast activation protein-α (FAP) and the angiogenesis marker cluster of differentiation 31 (CD31) in human cancer tissues of different origins. In the cohort studied, we found no correlation between disease stage and the expression of FAP or CD31. However, we have identified a clear correlation between pmCiC expression in cancer cells and cancer-associated stroma with tumour stage. It can be concluded that pmCiC is increased in cancer cells and in cancer-supporting cells in the tumour microenvironment at the later stages of cancer development, particularly at the metastatic sites. Therefore, pmCiC expression has the potential to serve as a prognostic marker, although further studies are needed.